2011
DOI: 10.1523/jneurosci.0077-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Corticothalamic Feedback Controls Sleep Spindle Duration In Vivo

Abstract: Spindle oscillations are commonly observed during stage two of non-REM sleep. During sleep spindles, the cerebral cortex and thalamus interact through feedback connections. Both initiation and termination of spindle oscillations are thought to originate in the thalamus, based on thalamic recordings and computational models, although some in vivo results suggest otherwise. Here, we have used computer modeling and in vivo multisite recordings from the cortex and the thalamus in cats to examine the involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
175
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(197 citation statements)
references
References 60 publications
(93 reference statements)
18
175
1
3
Order By: Relevance
“…Yet, the cortical (blue) feedback is essential to provide synchronization and spatial coherence of spindling over widespread thalamic regions [48]. More recently, a cortical control of intra-and inter-spindle periods has been postulated [128]. Three distinct phases can be distinguished in sleep spindles, as consistently shown by in vivo intracellular recordings.…”
Section: Box 3 Outstanding Questionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Yet, the cortical (blue) feedback is essential to provide synchronization and spatial coherence of spindling over widespread thalamic regions [48]. More recently, a cortical control of intra-and inter-spindle periods has been postulated [128]. Three distinct phases can be distinguished in sleep spindles, as consistently shown by in vivo intracellular recordings.…”
Section: Box 3 Outstanding Questionsmentioning
confidence: 98%
“…The involvement of increased corticothalamic feedback in provoking these paroxysmal oscillations was confirmed in ferrets [125,126]. Subsequent computational work suggested a cortical contribution to spindle termination: asynchronous cortical firing during the waning phase depolarizes TC cells, thereby 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 inactivating T currents [127,128]. A very recent modeling study implements TC matrix and core pathways, equivalent to distributed and focal projections, respectively, to show that global and local spindle detection may result from preferential monitoring of superficial and deeper cortical layer activity, respectively [56].…”
Section: Box 2 Exploring the Mechanisms Of Spindle Generation With Cmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular network level, a large body of studies employing multiunit recordings in animals and computational models has shown that spindles reflect oscillatory activity in widespread thalamocortical (TC) circuits. Although the neural circuitry that supports spindle generation is well known (Steriade, 2005) and involves a complex interaction between reticular (RE), TC, and pyramidal cells, more recent experimental evidence (Bonjean et al, 2011) suggests that corticothalamic input initiates spindles by triggering spike bursts in RE thalamic neurons and is maintained by synchronized firing in the RE-TC-RE circuit (Steriade, Nunez, & Amzica, 1993;von Krosigk, Bal, & McCormick, 1993). Spindles are terminated by desynchronization of the interaction between thalamic and cortical neuronal firing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, spindle frequency rhythms are seen in the isolated TRN 54,55 , but not in the isolated cortex or other thalamic nuclei 55,56 . Cortical feedback to the TRN and thalamocortical neurons, however, synchronizes spindles across cortical regions 57,58 and can initiate and terminate spindles 59 . Thus, in the intact brain, both spindles and SWs are the products of thalamocortical circuits.…”
Section: Discussionmentioning
confidence: 99%